Endophilin A2 regulates B‐cell endocytosis and is required for germinal center and humoral responses. (29th July 2021) - Malinova, Dessislava; Wasim, Laabiah; Newman, Rebecca; Martínez‐Riaño, Ana; Engels, Niklas; Tolar, Pavel
Abstract: Antigen‐specific B‐cell responses require endosomal trafficking to regulate antigen uptake and presentation to helper T cells, and to control expression and signaling of immune receptors. However, the molecular composition of B‐cell endosomal trafficking pathways and their specific roles in B‐cell responses have not been systematically investigated. Here, we report high‐throughput identification of genes regulating B‐cell receptor (BCR)‐mediated antigen internalization using genome‐wide functional screens. We show that antigen internalization depends both on constitutive, clathrin‐mediated endocytosis and on antigen‐induced, clathrin‐independent endocytosis mediated by endophilin A2. Although endophilin A2‐mediated endocytosis is dispensable for antigen presentation, it is selectively required for metabolic support of B‐cell proliferation, in part through regulation of iron uptake. Consequently, endophilin A2‐deficient mice show defects in GC B‐cell responses and production of high‐affinity IgG. The requirement for endophilin A2 highlights a unique importance of clathrin‐independent intracellular trafficking in GC B‐cell clonal expansion and antibody responses. Synopsis: A genome‐wide screen reveals a new clathrin‐independent mechanism of antigen uptake in B lymphocytes. The pathway is regulated by endophilin A2, a protein essential for germinal centre expansion and antibody responses. Genome‐wide CRISPR screens identify genes regulating antigen uptake in B cells, revealing key roles of both epsin1‐ dependent clathrin‐coated pits and a novel fast endophilin A2‐mediated endocytosis. Endophilin A2 is recruited to the B cell receptor after antigen binding in a signaling‐dependent manner. Endophilin A2 is required for peripheral B cell development, antigen‐specific germinal center responses and high‐affinity IgG production, in part through regulation of iron uptake. Abstract : A genome‐wide screen reveals a new clathrin‐independent mechanism of antigen uptake in B lymphocytes. The pathway is regulated by endophilin A2, a protein essential for germinal centre expansion and antibody responses.